Vortical Flow Structure in the Wake of an Estate Car (Communications in Computational Physics, 2020)
A finite volume simulation of unsteady vortical wake flow behind a square-backestate car is presented. The three-dimensional time-averaged incompressibleNavier-Stokes equations are solved together with the Reynolds stress transport equationsfor turbulence. By virtue of the simulated surface streamlines, the physics offluid can be extracted using the topological theory. In addition, the simulated topologicalsingular points and lines of separation are plotted on the car surface. The vorticalflow motions that developed behind the mirrors, wheels and car body are explored bymeans of the simulated time evolving vortex corelines. The formation and interactionof the vortex systems in the wake are examined by tracing the instantaneous streamlinesin the vicinity of the simulated vortex corelines. The vortex street behind theestate car is also illustrated by the simulated streaklines. Finally the Hopf bifurcationphenomenon is revealed by the time-varying aerodynamic forces on the car.